M20 Development of the new zealand bronchiectasis registry. (12th November 2019) - Diggins, B; Good, W; Dawkins, P; Poot, B; Stroil-Salama, E; Morgan, L; Wong, CA
Abstract : Introduction: The prevalence of bronchiectasis in New Zealand (NZ) is higher than comparable countries (180/100, 000 population) 1 ; the burden and severity of disease are incompletely understood. Bronchiectasis registries such as EMBARC (>14, 000 participants) and the Australian Bronchiectasis Registry (ABR, 1360 participants) have improved understanding of bronchiectasis and identified future research priorities. The aim of the NZ Bronchiectasis Registry (NZBR) is to contribute to the understanding of bronchiectasis aetiology and management, both in NZ and internationally. It is closely aligned with ABR and supported by Lung Foundation Australia. Methods: NZBR shares data fields with ABR and EMBARC, with additional fields to reflect unique socio-demographic characteristics of NZ participants. NZBR is a multi-centre, prospective, observational study enrolling consecutive patients in NZ. Participants are identified from existing clinical and research databases, and from inpatient and outpatient encounters. Eligible adult participants have a clinical diagnosis of bronchiectasis, excluding cystic fibrosis, confirmed on CT thorax. All participants are seen face-to-face and provide written consent. Demographics, clinical information, exacerbation history (including antibiotic prescription data) and health-related quality of life assessment are collected at enrolment and annual review. Data is entered into a secure online platform, which sits alongside ABR in REDCap. Results: National ethical approval is in place. Enrolment began at the primary site in June 2018, shortly followed by a second site. Two additional sites have local research governance approval. To date, 117 participants have been enrolled across 2 sites: 63/117 females (53.8%); mean age 62.4 (±15.6) years. 45/117 (38.4%) of participants are of M&x0101;ori or Pacific Island origin; 41/117 (35.0%) participants live in the most deprived socioeconomic quintile. Conclusion: These early steps have paved the way for a national bronchiectasis registry and are an early indicator of health inequalities for bronchiectasis in NZ. NZBR will contribute to a regional Australasian Bronchiectasis Registry to create a comprehensive longitudinal dataset across Australia and NZ, to help establish the burden of disease, promote changes in clinical practice and improve clinical outcomes. Future plans include addition of paediatric sites and increased collaboration with international registries. Reference: Telfar Barnard L, Zhang J. Asthmaand Respiratory Foundation New Zealand; 2017.